COMPARATIVE ANALYSIS OF qPCR MEASUREMENT OF HIV VIRAL LOAD AND ELISA DETECTION OF p24 ANTIGEN AFTER HYPERBARIC OXYGEN EXPOSURE - Budiarti, Retno; Kuntaman, Kuntaman; Suryokusumo, Suryokusumo; Khairunisa, Siti (African Journal of Infectious Diseases (AJID), 2020)
Background: A decrease in the number of viruses or viral nucleic acid components will determine whether a therapy successfully eradicates the virus. Sensitivity and specificity are needed to enable easy, precise and efficient diagnosis and evaluation of therapy. This study examined the sensitivity of quantitative PCR (qPCR) for detecting viral nucleic acids as compared with enzyme-linked immunosorbent assay (ELISA) for detecting the human immunodeficiency virus 1 (HIV-1) p24 antigen after hyperbaric oxygen therapy. Methods: The researchers isolated peripheral blood mononuclear cells (PBMCs) from healthy whole blood and inoculated HIV-1/MT4 virus in PBMC cultures. The cultures were exposed to hyperbaric oxygen at 2.4 ATA with 100% O2 for 3 × 30 minutes for 5 days. ELISA and qPCR were used to measure the p24 antigen and HIV-1 mRNA, respectively, in the treatment and control groups. Result: The amounts of p24 antigen and HIV-1 mRNA were significantly different (p = 0.001, p < α). The two examination methods were significantly different. Hyperbaric oxygen therapy can reduce virus numbers, as observed from the p24 antigen and HIV-1 mRNA levels. The treatment group had significantly lower virus numbers than the control group. HIV-1 mRNA detection is more sensitive than p24 antigen detection. Conclusion: Both qPCR and ELISA have their advantages, depending on whether the goal is to establish, diagnose or monitor antiretroviral therapy or to evaluate disease progression.